The Westerly Index as complementary indicator of the North Atlantic oscillation in explaining drought variability across Europe - Vicente Serrano, Sergio M.; García Herrera, Ricardo; Barriopedro, David; Azorín-Molina, César; López-Moreno, Juan I.; Martín-Hernández, Natalia; Tomás-Burguera, Miquel; Gimeno, Luis; Nieto, Raquel (Climate Dynamics, 2015)
43 páginas, 1 tabla, 9 figuras This paper analyses the influence of different atmospheric circulation indices on the multi-scalar drought variability across Europe by using the Standardized Precipitation Evapotranspiration Index (SPEI). The monthly circulation indices used in this study include the North Atlantic oscillation (NAO), the East Atlantic (EA), the Scandinavian (SCAN) and the East Atlantic–Western Russia (EA–WR) patterns, as well as the recently published Westerly Index (WI), defined as the persistence of westerly winds over the eastern north Atlantic region. The results indicate that European drought variability is better explained by the station-based NAO index and the WI than by any other combination of circulation indices. In northern and central Europe the variability of drought severity for different seasons and time-scales is strongly associated with the WI. On the contrary, the influence of the NAO on southern Europe droughts is stronger than that exerted by the WI. The correlation patterns of the NAO and WI with the SPEI show a spatial complementarity in shaping drought variability across Europe. Lagged correlations of the NAO and WI with the SPEI also indicate enough skill of both indices to anticipate drought severity several months in advance. As long as instrumental series of the NAO and WI are available, their combined use would allow inferring European drought variability for the last two centuries and improve the calibration and interpretation of paleoclimatic proxies associated with drought. The authors wish to acknowledge Ricardo Trigo and one anonymous reviewer for their detailed and helpful comments to the original manuscript. The data for this paper are available at Spanish National Research Council repository (http://sac.csic.es/spei/database.html), at Climate Research Unit (http://www.cru.uea.ac.uk/cru/data/nao/) and the Climate Prediction centre of the NOAA (http://www.cpc.ncep.noaa.gov/data/teledoc/telecontents.shtml). This work was supported by the research project ...